2017
DOI: 10.1136/bmjopen-2017-019037
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum uric acid and atrial fibrillation: a cross-sectional community-based study in China

Abstract: ObjectivesTo investigate the effects of gender on the association of serum uric acid (SUA) levels and atrial fibrillation (AF) prevalence in a community-based Chinese population.SettingData were obtained from annual Jidong Oilfield employee and family member health checkups. The Jidong community is geographically located in Tangshan City in northern China.ParticipantsA total of 9078 residents were invited to take part in the survey and provided informed consents. Individuals without data of ECG or SUA were exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…As a regional study, the prevalence of our result was similar to other regional investigations in China. [15][16][17][18] However, our prevalence was relatively lower than that in Qingdao, Shandong Province, which is close to the sea and where residents consume high amounts of seafood and beer. 28 Moreover, the prevalence of HUA in our population was lower than those in the USA and Japan, 12 29 which might be attributed to economic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a regional study, the prevalence of our result was similar to other regional investigations in China. [15][16][17][18] However, our prevalence was relatively lower than that in Qingdao, Shandong Province, which is close to the sea and where residents consume high amounts of seafood and beer. 28 Moreover, the prevalence of HUA in our population was lower than those in the USA and Japan, 12 29 which might be attributed to economic status.…”
Section: Discussionmentioning
confidence: 99%
“…15 In 2017, Chen et al found that the prevalence of HUA was 13.4% in Jidong community of Tangshan City in northern China. 16 In an elderly Chinese population of 7 areas, the overall prevalence of HUA was 13.1% in 2018. 17 Liu et al 18 also conducted a meta-analysis including 38 regional studies between 2000 and 2014 to determine the prevalence of HUA in mainland China.…”
Section: Introductionmentioning
confidence: 99%
“…AF is the most common heart rhythm disorder, and its major risk factors include advanced age, hypertension, obesity, diabetes, HF, valvular heart disease, and MI. In recent years, numerous clinical studies have confirmed that hyperuricemia is associated with AF after adjusting for various cardiovascular risk factors, and the correlation is stronger in women than in men (Liang et al, 2016;Zhang et al, 2016;Chen et al, 2017;Kuwabara et al, 2017c;Mantovani et al, 2018;Pak et al, 2018;Black-Maier and Daubert, 2019;Lin et al, 2019). The bases for sex-related differences in high UA and AF or CHD remains unknown.…”
Section: Ua and Afmentioning
confidence: 99%
“…SUA is the final product of purine metabolism catalyzed by xanthine oxidase, which plays an important role in the formation of free radical superoxide anion and oxidative stress, consequently resulting in calcium overload and decreasing sodium channels and aggravating cellular damage (8)(9)(10). These pathological processes promote electrical remodeling and structural remodeling of the left atrium, leading to an increase of its size and contribute to the occurrence and development of AF (11)(12)(13)(14)(15). High SUA level is an independent risk factor for stroke and cardiovascular death (16)(17)(18)(19).…”
Section: Main Findingsmentioning
confidence: 99%